2005
DOI: 10.1111/j.1348-0421.2005.tb03684.x
|View full text |Cite
|
Sign up to set email alerts
|

Close Correlation of Streptococcal DNase B (sdaB) Alleles with emm Genotypes in Streptococcus pyogenes

Abstract: Streptococcal DNases are major exoenzymes and possible virulence factors in Streptococcus pyogenes and are classified into four types: DNase A, B, C and D. Among these DNases, DNase B, which is also designated as mitogenic factor (MF) or streptococcal pyrogenic exotoxin F (speF) (3,4), is dominant, although its role in the pathogenesis of S. pyogenes has not been well elucidated. S. pyogenes strains commonly express DNase B, but the other three DNases are not frequently expressed and thus DNase B has a major s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The NETs degradation inhibition assay showed that, similar to the M1 culture supernatant, the supernatant from M3.11 culture degraded NETs and the degradation was prevented by rabbit anti-Sda1 IgG (Figure 5B). To confirm Sda1 anti-serum can recognize other GAS DNases, recombinant DNase B, a DNase frequently expressed in most GAS strains [28], was generated. Western blot revealed that Sda1 antiserum cross-reacted with the recombinant DNase B (26.7 kD) (Figure 5C).…”
Section: Anti-sda1 Prevented Nets Degradation and Mucosal Infection B...mentioning
confidence: 99%
“…The NETs degradation inhibition assay showed that, similar to the M1 culture supernatant, the supernatant from M3.11 culture degraded NETs and the degradation was prevented by rabbit anti-Sda1 IgG (Figure 5B). To confirm Sda1 anti-serum can recognize other GAS DNases, recombinant DNase B, a DNase frequently expressed in most GAS strains [28], was generated. Western blot revealed that Sda1 antiserum cross-reacted with the recombinant DNase B (26.7 kD) (Figure 5C).…”
Section: Anti-sda1 Prevented Nets Degradation and Mucosal Infection B...mentioning
confidence: 99%